Epigenetics of multiple myeloma after treatment with cytostatics and gamma radiation - Krejcí, Jana; Harnicarová, Andrea; Streitová, Denisa; Hájek, Roman; Pour, Ludek; Kozubek, Stanislav; Bártová, Eva (Leukemia research, 2009)
Genetic and epigenetic changes in multiple myeloma (MM) correlate with the stage of the disease. Therefore, we investigated how cytostatics and gamma radiation influence MM-associated histone modifications. ChIP-PCR and ChIP-on-chip technologies were used to quantify H3K9 acetylation and H3K9 dimethylation at select loci in MM patients, lymphoblastoid ARH-77, and myeloma MOLP-8 cells. Genome-wide analysis revealed that the cytostatic, melphalan, increased H3K9 acetylation at multiple gene promoters in ARH-77 cells. Melphalan and gamma radiation also influenced histone modification of prognostically important c-myc and CCND1 genes in ARH-77 and MOLP-8 cells. Moreover, H3K9 acetylation at c-myc and CCND1 promoters was increased in individual MM patients after melphalan treatment. Western blotting revealed that these effects were accompanied by changes in c-MYC and cyclin D1 protein levels. Taken together, we showed that cytostatics significantly alter histone modification of tumor-related genes which is indispensable for understanding cancer therapies.
Keywords: záření gama; Chromatin Immunoprecipitation; proliferace buněk; apoptóza; Base Sequence; Gamma Rays; geny myc; kombinovaná terapie; chromatinová imunoprecipitace; průtoková cytometrie; cyklin D1; polymerázová řetězová reakce; Polymerase Chain Reaction; Apoptosis; lidé; Antineoplastic Agents; Genes, myc; protinádorové látky; mnohočetný myelom; Flow Cytometry; DNA primery; Cyclin D1; epigeneze genetická; Combined Modality Therapy; sekvence nukleotidů; Cell Proliferation; DNA Primers; Multiple Myeloma; Epigenesis, Genetic; Humans